Audit Sistem Jubelio Pada Perusahaan Peralatan Elektronik Menggunakan Domain Service Design ITIL V3 - Bernanda, Devi Yurisca; Widjaja, Michelle Disa; Sutria, Kevin; Rahman, Muhammad Ryo; Andry, Johanes Fernandes (JURNAL FASILKOM, 2023)
Electronic equipment companies in Jakarta have used information technology (IT) for daily operational activities, the IT used is an application or Jubelio system to support the smooth running of the organization in supporting its business needs, with the help of this IT equipment it is hoped that it will improve its service both internally such as employees and management as well as external customers, namely. Because the system has been implemented for so long, an audit of the application is needed using the ITIL V3 standard. This standard is used to see the extent of IT's success in carrying out its functions and will also carry out a design review of additions to the Jubelio system. This service helps companies gain a better understanding of the need for additional features for applications, and the future challenges faced by users at the company. Of course, this all involves users within the organization in the design process. The final result of the Jubelio application audit is that the company received recommendations from researchers, namely improving IT services even better, showing that Service Catalog Management, Service Level Management, Capacity Management, Availability Management, IT Service Continuity Management, Information Security Management, and Supplier Management is at the current level of 1.43 to 2.75, from the expected level of 3.00 with a gap between 0.25 to 1.67.